Iron (II) and other heavy-metal tolerance in bacteria isolated from rock varnish in the arid region of Al-Jafer Basin, Jordan - SULAIMAN ALNAIMAT; SAQER ABU SHATTAL; OSAMA ALTHUNIBAT; EID ALSBOU; REDA AMASHA (Biodiversitas Journal of Biological Diversity, 2017)
Alnaimat S, Shattal SA, AlthunibatO, Alsbou E, Amasha R. 2017. Iron (II) and other heavy-metal tolerance in bacteria isolated from rock varnish in the arid region of Al-Jafer Basin, Jordan. Biodiversitas 18: 1250-1257. This study deals with enumeration, identification and molecular characterization of bacterial species tolerant of iron (II) and other heavy metals that isolated from rock varnish collected from the arid region of Al-Jafer Basin, Jordan. Based on conventional culture-dependent methods, six isolates exhibited a high degree of tolerance to iron (II) and other heavy metals with a minimum inhibitory concentration (550â€“600 mg/L) to iron, (500-550 mg/L) to lead, (350 mg/L) to copper, (400-450 mg/L) to chromium, (150-200 mg/L) to silver, and (150-200 mg/L) to mercury, in solid media. The results showed that all isolates could tolerate 2000 mg/L Fe2+ expressed as maximum tolerance concentration (MTC). The multiple metal resistances of these isolates were also associated with multiple antibiotic resistances. These iron tolerant isolates were shown to be capable of growth at temperatures ranging from 30 to 40Â°C and pH values ranging from 5 to 9 with some differences between the six isolates. On the basis of morphology and of 16S rDNA gene sequencing and phylogeny analysis, the iron-tolerant isolates were identified as Bacillus zhangzhouensis (DVCr1), Staphylococcus warneri (DVCr6), Bacillus cereus (DVCr7), Staphylococcus pasteuri (DVCu2), Brevibacterium frigoritolerans (DVPb) and Bacillus altitudinis (DVCr10). The 16S rDNA sequences from five of the six strains were submitted to GenBank and are available under the accession numbers KX781139, KX781140, KX781141, KX781145 and KX781148. The results highlight the high potential of a non-polluted habitat like rock varnish to provide new microbial communities that could be used for enhanced bioremediation of heavy metals from a contaminated site.